Crossing Y-Solitaire thrombectomy as a rescue treatment for refractory acute occlusions of the middle cerebral artery. (7th September 2018) - Aydin, Kubilay; Barburoglu, Mehmet; Oztop Cakmak, Ozgur; Yesilot, Nilufer; Vanli, Ebru Nur Yavuz; Akpek, Sergin
Abstract : Background: Mechanical thrombectomy using a stent retriever has become the standard of care for acute large-vessel occlusions in the anterior circulation. Clots that are refractory to single stent retriever thrombectomy remain a challenge for neurointerventionalists. Objective: To assess the efficacy and safety of double stent retriever (crossing Y-Solitaire) thrombectomy as a rescue treatment for acute middle cerebral artery (MCA) occlusions that are refractory to single stent retriever thrombectomy. Methods: We retrospectively reviewed the databases of our hospitals to identify patients who presented with an acute MCA occlusion and were treated with crossing Y-Solitaire thrombectomy. The angiographic (Thrombolysis in Cerebral Infarction (TICI) scale) and clinical outcomes (National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS) scores) and complications were assessed. Results: Ten patients were included in the study. The median initial NIHSS score and Alberta Stroke Program Early CT Score (ASPECTS) were 19.0 and 9.6, respectively. Crossing Y-Solitaire thrombectomy was performed as a rescue technique after unsuccessful single Solitaire thrombectomy passes in all cases. Successful recanalization (TICI 2b/3) was achieved in 8 (80%) patients. We observed asymptomatic reperfusion hemorrhages in 2 (20%) patients. No procedural related complications were seen other than reversible vasospasms in 5 (50%) patients. Sixty percent of the patients had a mRS score of between 2 and 0 at 90 days after the procedure. There was no mortality. Conclusion: Crossing Y-Solitaire thrombectomy seems to be an effective and safe alternative rescue technique to treat refractory MCA bifurcation occlusions that are refractory to standard thrombectomy procedures.